Implementasi Program Penelitian dan Pembangunan Daerah Di Bidang Litbang Badan Perencanaan Pembangunan Daerah (BAPPEDA) Kabupaten Situbondo - Fahrudin Fahrudin; Moh. Ulil Absor Hamdani; Abdul Qodir; Ali Mundzir (CV. Ulil Albab Corp, 2025)
The aim of this research is to determine the implementation of the Research and Development (R&D) Program at the Agency Situbondo Regency Regional Development Planning (Bappeda) in 2024, and knowing the driving and inhibiting factors for the Implementation of the Research and Development (R&D) Program at the Situbondo Regency Regional Development Planning Agency in 2024.Using qualitative descriptive research methods, with method collecting data obtained from field observations, interviews with several informants from the Head of Division, Head of Sub-Division, to staff. Then literature study obtained from various regulations and documentation.The inhibiting factor encountered during the implementation or implementation of programs in the R&D sector is the diversity of understanding, perception and background of each employee giving rise to points of view in each discussion/discussion forum. The second obstacle is that variations in the volume and target level of work difficulty cause varying completion times, also due to the capacity of employees in a work unit. The supporting factor obtained is that the performance in the R&D sector has all been regulated in Perbup Number 41 of 2022 concerning SOTK Bappeda Situbondo Regency, so that staff can carry out their respective duties without overlapping. The performance of the staff and good communication between staff also creates a harmonious work environment.